Kontribusi Kinerja Kelompok Swadaya Masyarakat (KSM) dengan Kepuasan Masyarakat dalam Pengelolaan Sampah - Zuhrina Aidha; Delfriana Ayu (Journal of Telenursing (JOTING), 2022)
This study aims to identify the performance of KSM Pondok Miri Asri, community satisfaction, and the relationship between the performance of KSM Pondok Miri Asri with community satisfaction in managing waste in Sunggal District, Deli Serdang Regency as a form of mosque-based community empowerment post (Posdaya Masjid). The method used is a mixed method. Informants in this study were Sunggal sub-district officers, Sei Semayang Village officers, the chairman of the Ar-Ridho Mosque Prosperity Agency and the community. The results showed that as many as 61% of respondents stated that the performance of KSM Pondok Miri Asri was classified as good and 62.7% said they were satisfied with the performance. The significance value obtained is <0.05. In conclusion, the performance of KSM Pondok Miri Asri and community satisfaction are categorized as good, and there is a significant relationship between the performance of KSM Pondok Miri Asri and community satisfaction in Sunggal District. Keywords: Satisfaction, Performance, Empowerment, Garbage